Tutti pazzi per il legal drama. Uno sguardo semiotico sulle dinamiche processuali nella serialità televisiva - Antonia Cava (Funes)
The contribution analyzes the analogies and connections between legal and communicative phenomena, using legal-drama as a case study. Considering the legal system as a semiotic system, we will describe the image of law portrayed by TV writing. We will reconstruct, in particular, the dynamics of the spectacularization of the trials in some of the TV series that have been widely successful both nationally and internationally. The analysis of the imagery constructed by TV series around the judicial system will also allow us to reflect on the effects that legal audiovisual products may have on the perception of legal reality. In the conclusions we will propose an explanation of the success of TV series depicting the law. The enormous interest generated by television series set in courtrooms, in fact, finds a possible explanation in the exciting confrontation between justice and injustice.